(untitled) (Bioresearch Communications, 2026)
Purpose: The purpose of this study was to explore the major psychosocial challenges faced by adolescents in Bangladesh and to identify the coping strategies they adopt to manage these challenges. Recognizing adolescence as a critical period of psychological, emotional, and social development, the study aims to provide insight into how family dynamics, social environments, and cultural expectations influence adolescent mental health and well-being. Methodology: A qualitative research design was adopted to gain an in-depth understanding of adolescents lived experiences. Data were collected through four individual in-depth interviews (IDIs) and five focus group discussion (FGD) with adolescents aged 13–18 years from schools in Dhaka City. Participants were selected purposively to ensure diversity of experiences. Thematic and content analysis techniques were applied to identify recurring psychosocial patterns, emotional struggles, and coping mechanisms. Findings: The findings reveal that Bangladeshi adolescents frequently experience stress, anxiety, and depressive symptoms resulting from restrictive parenting, excessive academic pressure, limited personal freedom, and lack of emotional support. Communication barriers between parents and children, gender-based restrictions, and social stigma further exacerbate these challenges. Despite these difficulties, adolescents adopt a range of coping mechanisms, including seeking social support, engaging in extracurricular and religious activities, and problem-focused coping. However, maladaptive behaviours such as withdrawal and substance use were also observed among those lacking guidance or mental health resources. Implications: The study underscores the urgent need for school-based counselling, improved parent–adolescent communication, and community-level mental health initiatives. By framing the psychosocial challenges of Bangladeshi adolescents within a global context, it highlights the importance of integrating mental health awareness into education and family systems to foster resilience and support healthier adolescent development. Conclusion: In conclusion, the study highlights that adolescence, though a vulnerable stage, offers significant potential for growth when supported by understanding families and inclusive environments. Strengthening mental health awareness, parental communication, and school-based support can foster resilience and emotional stability among Bangladeshi adolescents. Bioresearch Commu. 12(1): 2070-2077, 2026 (January)